Holocene stalagmite δ18O records in the East Asian monsoon region and their correlation with those in the Indian monsoon region. (December 2014) - Yang, Xunlin; Liu, Jianbao; Liang, Fuyuan; Yuan, Daoxian; Yang, Yan; Lu, Yanbin; Chen, Fahu
We compare well-dated Holocene stalagmite δ 18 O records from the East Asian Summer Monsoon (EASM) region and from the Indian Summer Monsoon (ISM) region. We found that the pattern of latitudinal change of speleothem δ 18 O values from the Indian monsoon region to the East Asian monsoon region is almost identical to that of modern precipitation. This suggests that the modern moisture transport route from the Indian Ocean to the East Asian monsoon region has existed since at least the early Holocene. The δ 18 O records from both regions exhibit a remarkably similar trend of variation in that the values are more negative during the early Holocene, rapidly become heavy from the mid-Holocene, and are heaviest during the late Holocene. The stalagmite δ 18 O changes in the East Asian monsoon region are statistically well correlated with those in the Indian monsoon region, both over the entire Holocene and in detail over the last 2000 years. However, in contrast to the obvious consistency of the δ 18 O values in all of the speleothem records, both instrumental and historical climate records indicate significant spatial variations in rainfall over eastern China. The early-Holocene strong EASM pattern referred from speleothem δ 18 O in the East Asian monsoon region is quite different to that of other paleoclimatic records such as Holocene paleosol development in the Chinese Loess Plateau, eolian activity in the northern Chinese sandlands, and lake sediments in EASM-dominated region in China, in which the strongest EASM was documented during the mid-Holocene. These findings suggest that the speleothem δ 18 O record from the East Asian monsoon region may not record EASM variability, but rather that it is controlled by variations in the isotopic composition of precipitation, which is determined mainly by rainfall variability in the ISM region.